Adiposity-Induced Voiding Dysfunction: Unraveling the Association Between Overweight Status and Symptom Severity in Non-Retentive Benign Prostatic Hyperplasia - Iman Hakim Wicaksana; Setya Anton Tusarawardaya; Suharto Wijanarko; Wibisono; Amru Sungkar (Open Access Indonesian Journal of Medical Reviews, 2026)
Benign prostatic hyperplasia (BPH) has historically been viewed through a prostato-centric lens, attributing lower urinary tract symptoms (LUTS) primarily to prostatic volume and mechanical obstruction. However, this model fails to account for the substantial symptom burden observed in patients without significant retention or massive enlargement. Emerging evidence suggests that systemic metabolic dysregulation, particularly adiposity, plays a crucial role in the pathophysiology of LUTS. This study aims to evaluate the association between Overweight status and the subjective severity of LUTS in a specific cohort of non-retentive BPH patients, thereby isolating metabolic contributors from acute mechanical failure. We conducted an observational analytic cross-sectional study at the Urology Polyclinic of RSUD Dr. Moewardi, Surakarta, Indonesia, from June 2024 to January 2025. The study enrolled 110 men diagnosed with BPH who met strict criteria for non-retentive status (post-void residual <150 mL, no indwelling catheter). Participants were stratified into normal BMI (<25 kg/m²) and Overweight (≥25 kg/m²) groups. Symptom severity was quantified using the International Prostate Symptom Score (IPSS). Data were analyzed using the Mann-Whitney U test and Chi-square analysis. The cohort comprised 72 (65.5%) normal-weight and 38 (34.5%) overweight patients. A statistically significant disparity in symptom severity was observed. The overweight group exhibited a significantly higher mean IPSS (17.87 ± 5.18) compared to the normal group (11.54 ± 4.71) (p<0.001). Notably, 44.7% of overweight patients presented with severe LUTS, compared to only 5.6% of normal-weight patients. Conversely, 90.9% of patients with mild symptoms belonged to the normal-weight group. In conclusion, overweight status is significantly associated with increased LUTS severity in non-retentive BPH patients. The findings suggest that adiposity exacerbates voiding dysfunction through systemic inflammatory, hormonal, and autonomic pathways independent of urinary retention. These results advocate for the integration of weight management as a core therapeutic strategy in BPH care.